Athletic Identity Indicators among Athletes with Physical Disabilities - Matelionytė, Karolina; Skučas, Kęstutis; Pukėnas, Kazimieras (Special Education, 2026)
The aim of the study was to determine how various factors (gender, age, place of residence, origin of disability, age at disability onset, frequency of sports participation, and duration of sports participation) are associated with athletic identity among athletes with physical disabilities. The study was conducted in 2024–2025 during the Lithuanian Disabled Sports Championships organized by the Lithuanian Sports Federation for the Disabled. Data were collected by using a standardized questionnaire, the Athletic Identity Measurement Scale (AIMS). The study involved 122 athletes with physical disabilities. Nonparametric statistical methods were used for data analysis.The results revealed statistically significant differences in overall athletic identity only by gender. Across age groups, the overall athletic identity did not differ significantly, however, differences were found at the level of a single item. The place of residence, origin of disability, age at disability onset, frequency of sport participation, and duration of sport participation were not significantly associated with one’s athletic identity. These findings suggest that athletic identity among athletes with physical disabilities is not directly related to most demographic or sport participation intensity variables; yet, it may instead be more strongly associated with subjective sport experience.